Plasticization conditions and strength of a welded beam-to-column connection in case of various detailing. (15th June 2018) - Vacev, Todor; Paunović, Stepa; Nešović, Ivan; Zorić, Andrija; Milić, Miloš
Highlights: Typical welded beam-to column connection was analysed using EC methodology and FEA. FEA was done in materially nonlinear domain with fully 3D modelling of the weld. Results revealed stress concentrations and plasticization regions neglected by EC. Plasticization should be introduced into the design process if precisely determined. Different construction detailing, was also analysed, with guidelines for practice. Abstract: Beams and columns in steel structures are regularly connected using bolted or welded connections. In this paper, one typical welded connection was analysed using Eurocode standard methodology and advanced finite element (FE) analysis in materially nonlinear domain with fully 3D modelling of the fillet weld. The FE analysis revealed stress concentrations and plasticization regions, which are out of reach in Eurocode methods. Those phenomena were the main source of disagreement in weld strength obtained by the two methods. Since the classical solutions admit existence of the stress concentrations and plasticization, but do not take them into calculation, an attempt was made to investigate them and to introduce them into the design process, proposing a controlled degree of plasticization. Such methodology is not part of established codes, and it was not given here as a solution ready-to-use, but as an open question for a broader research, pointing out at the phenomena that are neglected by classical design methods. Besides that, the subject of research was the influence of the column flange thickness on connection strength, as well as different construction detailing, including some non-standard solutions.